Evaluating Learning Community Programs for Teacher Professionalism Using the Cipp Model - Ibnu Muthi; Imam Suseno (Jurnal Pendidikan Terapan, 2026)
n the era of disruption and the 4.0 industrial revolution, educators should think about the balance of hard skills and soft skills to avoid boring and demagogic learning processes, which might decrease human dignity. This research is aimed at in-depth evaluation of the efficiency of the "JERMAN GC" Learning Community (Kombel) at SMP Islam PB. Soedirman Bekasi as a platform for the transformation of the potential professionalism of teachers. The evaluation was conducted utilising the CIPP model (Context, Input, Process, Product) with a descriptive qualitative method. Data collection was done by observation, in-depth interviews, and document studies. Data analysis was done by using Miles and Huberman's interactive model. The research findings indicate that in terms of context, this program is very relevant to the teachers’ desires for a reflective collaborative space. On the input side, the existence of internal resource persons and comprehensive training materials provide a good basis. In terms of procedure, there is a steady managerial cycle of planning, implementation and successful peer coaching. In terms of product, the program was successful in improving teachers’ pedagogical competence, improving the quality of 4C-based learning (critical, creative, collaborative, communicative), and was considered to be very cost-effective. The outcome of this research is that Kombel “JERMAN GC” has successfully become the driving force for the reform of the learning culture in schools. This research has consequences, to the fact that community-based teacher professionalism development with minimum costs can have maximum impact on the quality of education, thus this approach is highly replicable by other educational institutions in developing an adaptive and innovative school ecosystem.